DETERMINANT FACTOR AND DEVELOPMENT OF STRATEGY MODEL OF TURNOVER INTENTION ON BANKING IN BENGKULU CITY (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This study aims to analyze the existing HR Practices and the behavior of OCB employees that are able to predict the factors causing the turnover intention of employee in Banking companies. Research method through quantitative approach, this research type is descriptive research and verificative research. Data collection techniques used questionnaires and documentation techniques. Source of data obtained through primary data and secondary data. The unit of analysis in this study Banking companies and observation units are conventional banking employees in Bengkulu City. The number of samples was determined using the Slovin formula so that obtained a sample of 311 respondents. The data analysis process used is SEM (Structural Equation Modeling). The results showed that HR Practices have a significant positive influence on OCB, HR Practice and OCB has a significant negative effect on Turnover Intention, while HR Practices through OCB has no effect on Turnover Intention.